2019
DOI: 10.1111/bjd.17858
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplant with post‐transplant cyclophosphamide for recessive dystrophic epidermolysis bullosa expands the related donor pool and permits tolerance of nonhaematopoietic cellular grafts

Abstract: Summary Background Recessive dystrophic epidermolysis bullosa (RDEB) is a severe systemic genodermatosis lacking therapies beyond supportive care for its extensive, life‐limiting manifestations. Objectives To report the safety and preliminary responses of 10 patients with RDEB to bone marrow transplant (BMT) with post‐transplant cyclophosphamide (PTCy BMT) after reduced‐intensity conditioning with infusions of immunomodulatory donor‐derived mesenchymal stromal cells (median follow‐up 16 months). Methods BMT to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…As for other cells with stem functionality, human umbilical cord blood-derived unrestricted somatic stem cells (USSCs) have shown anti-fibrotic effects and amelioration of disease phenotype in col7a1 −/− mice through the up-regulation of two relevant TGF-β1 antagonists: DCN and TGF-β3 [110,111,112]. However, pilot cell therapy trials on RDEB patients revealed modest to absent clinical efficacy and improvement in patient’s quality of life, low-tolerability or severe side effects [113,114,115,116,117].…”
Section: Dystrophic Ebmentioning
confidence: 99%
“…As for other cells with stem functionality, human umbilical cord blood-derived unrestricted somatic stem cells (USSCs) have shown anti-fibrotic effects and amelioration of disease phenotype in col7a1 −/− mice through the up-regulation of two relevant TGF-β1 antagonists: DCN and TGF-β3 [110,111,112]. However, pilot cell therapy trials on RDEB patients revealed modest to absent clinical efficacy and improvement in patient’s quality of life, low-tolerability or severe side effects [113,114,115,116,117].…”
Section: Dystrophic Ebmentioning
confidence: 99%
“…In each clinical trial 10 patients received intravenous infusions of hBM-MSCs [2× 10 6 cells/kg to 4 × 10 6 cells/kg ( Rashidghamat et al, 2020 )]. In the case of Ebens et al two of the transplants provoked veno-occlusive disease of the liver and 1 of the patients developed graft versus host disease ( Ebens et al, 2019 ). After 1 year of follow-up, skin biopsies showed stable ( n = 7) to improved ( n = 2) type VII collagen protein expression and gain of anchoring fibril components ( n = 3) ( Ebens et al, 2019 ) and total blister count over the entire body surface area showed a decrease compared with baseline ( Rashidghamat et al, 2020 ).…”
Section: Mesenchymal Stem Cells In Cutaneous Injuries or Diseasesmentioning
confidence: 99%
“…[ 42 ] However, even with minimum intensity conditioning protocols, morbidity and mortality still remain high (10%‐15%). [ 43,44 ] Addition of mesenchymal stem cell (MSC) infusions is currently being evaluated for an immunosuppressive effect, potentially allowing for a further attenuated conditioning regimen and lower peri‐interventional risks of immunomyeloablation. [ 45,46 ] (NCT02582775, NCT01033552) Apart from enhancing the safety and efficacy of the HSCT, MSCs may also serve as an additional source of renewable cells for the treatment of focal areas of residual blistering.…”
Section: Symptom‐relieving and Disease‐modifying Therapiesmentioning
confidence: 99%